Biogas production from traditional market waste to generate renewable energy; IFOST 2012; Vol. 1 - Sulistyo H. Hary; Syamsiah S. Siti; Herawati D. A. Dewi Astuti; Wibawa A. A. Andang Arif (Section 1. Chemical engineering and "Green technology", 2012)
The increased energy consumption and limited fossil energy sources caused industry to find energyfrom renewable resources. Biogas is one of the renewable energy that has a good prospect in the near future. Traditional market wastes which were represented by green mustard and white mustard were undertaken in a laboratory experiment. To produce biogas, the raw material such as white mustard and cow manure, green mustard and rice straws were mixed until C to N ratio close to 20. Inoculums starterfrom biodigester effluent was put into digester then water was added until 350 ml. The initial pH was measured. Fermentation process was conducted at temperature of 35°C. Volume and pH of the biogaswere observed daily. Methane, total solid and volatile solid were analyzed weekly. Fermentation process was observed for 7 weeks. The accumulation of biogas production at the day 42 for white mustard (S1), white mustard with cow manure (S2), and mixed of green mustard and rice straw (S3) were 0.111L, 0.901L and 0.390L respectively. The highest methane concentration in the biogas was achieved on the day 21, which were found of 62.18% and 63.15% for S2 and S3 respectively. Meanwhile for S1 (white mustard only without cow manure) no methane was observed. In the first 7 days, the pH level were observed decrease and increase after the day of 28. However, at the end of digestion period the pH will slightly decrease. It was also developed to conduct a pilot plant within the tubular digester to generate energy in batik home industry, Imogiri, Yogyakarta, Indonesia.